Problematika Keterwakilan Perempuan Paling Sedikit 30% dalam Pencalonan Anggota Legislatif - Agatha, Insani Tiara; Mustafid, Mustafid; Anwar, Alfiansyah (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2024)
Gender issues have become a separate discourse in the Indonesian legal system, which has even touched on aspects of the protection and representation of women in parliament due to the phenomenon of the relatively low representation of women members in parliament. Therefore, the government is making efforts to realize women's representation in parliament, which is then formulated in various legal frameworks. However, this affirmative policy actually creates problems in its implementation. This research uses a type of library research with a normative juridical research method that uses a conceptual approach and statutory regulations. The results of this research are that the provisions regarding women's representation of at least 30% in the nomination of legislative members are no longer relevant in implementation in Indonesia, because there is disorientation in their implementation.